Effect of storage management on judicial service delivery of law courts within Western region in Kenya - Khamadi, Bernard Alusa; Kwendo, Evans; Machuki, Kelvin (African Quarterly Social Science Review, 2026)
This study aimed to analyse the effect of storage management on service delivery of law courts within the Western Region, Kenya. The study was guided by Resource-Based View (RBV) theory. The study adopted a descriptive research design and targets a population of law courts, namely Bungoma, Busia, Butali, Butere, Hamisi, Kakamega, Kimilili, Malaba, Mumias, Port Victoria, Sirisia, Vihiga, and Webuye. The study used a census method where data was collected through administering questionnaires and conducting interview schedules. Descriptive and inferential statistics were used for data analysis. The Kisumu region was used to carry out a pilot study to ascertain the validity and reliability of the research instruments. Informed consent and confidentiality, which are ethical considerations, were observed during the study.  Version 25 of the Statistical Package for the Social Sciences (SPSS) was for Windows. Descriptive statistics analysis tools included statistical measures of central tendency, including arithmetic mean and standard deviation, which were reported in tables as frequencies and percentages. The content analysis was used to analyse qualitative data, and descriptive or inferential statistics were used to analyse quantitative data. As a fair test of the relationship and association between two independent variables on a dependent variable, inferential statistics parametrically tested the hypothesis using Pearson Product Moment Correlation and Multiple Regression Analysis as a suitable test. The study found a statistically significant relationship between storage management (P = 0.001) and service delivery; thus, the null hypothesis was accepted at a P-value ≤ 0.05. The study concludes that storage management significantly affects judicial service delivery. Its findings will benefit policymakers, the government, and all court users in Kenya's Western Region. It recommends that law courts invest more in technology and infrastructure to improve judicial service delivery for litigants. Courts should continue integrating with their supply chain partners to enhance organizational service delivery. The study also suggests further research on inventory management technologies, particularly for controlling stock during receiving, data reporting, and issuing from the store.